Cyprian and Women in a Time of Persecution - Dunn, Geoffrey D. (The journal of ecclesiastical history, 2006)
Cyprian believed that the maintenance of ecclesial disciplina was the prime responsibility of a bishop's pastoral ministry, particularly in a time of persecution when people's loyalty was under threat. Throughout his episcopate Cyprian ministered to women as well as men who experienced persecution. Not only was he attempting to secure socio-political support through patronage for his position as bishop but he was applying the prescriptions of the Gospels. He praised women who remained faithful as role models for others, instructed and encouraged them in their perseverance and aided them in their need. Women who lapsed were dealt with according to ecclesial disciplina no differently than were the men who lapsed. While lay women and men had their own share in pastoral ministry, the issue of what to do with lapsed Christians raised the question of the extent to which a bishop's responsibilities were primary. In some letters not by Cyprian we sense not only a greater degree of familiarity with lay people but less of a concern with the importance of disciplina. In response to a recent paper in this JOURNAL by Allen Brent, it is argued here that a close reading of these non-Cyprianic letters in the corpus reveals that the male and female confessors who wanted the lapsed to be reconciled did not consider themselves to be presbyters who could reconcile but thought of themselves as confessors with the right to tell the bishop of those whom he was to reconcile.